2004
DOI: 10.1097/01.ccm.0000147687.06808.92
|View full text |Cite
|
Sign up to set email alerts
|

Removal of linezolid by conventional intermittent hemodialysis, sustained low-efficiency dialysis, or continuous venovenous hemofiltration in patients with acute renal failure

Abstract: In patients with acute renal failure, serum levels of linezolid can be reduced to the subtherapeutic range following renal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 16 publications
1
57
1
1
Order By: Relevance
“…In contrast, two studies revealed either significantly reduced serum linezolid concentrations in critically ill patients on intermittent hemodialysis (IHD) [31] or serum concentrations of linezolid reduced to subtherapeutic values following renal replacement therapy [32]. Fiaccadori studied two patients on ED in which the ED session lasted 8-9 h, whereas the average time of ED in our study was 19.5 h. They also found an important fraction of the administered dose of linezolid was removed, especially in the case of IHD with ED.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, two studies revealed either significantly reduced serum linezolid concentrations in critically ill patients on intermittent hemodialysis (IHD) [31] or serum concentrations of linezolid reduced to subtherapeutic values following renal replacement therapy [32]. Fiaccadori studied two patients on ED in which the ED session lasted 8-9 h, whereas the average time of ED in our study was 19.5 h. They also found an important fraction of the administered dose of linezolid was removed, especially in the case of IHD with ED.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with prior reports (4), thrombocytopenia appeared to be duration dependent, occurring more frequently in those treated for greater than 14 days (0/13 versus 13/13, P Ͻ 0.001, Fisher's exact test). Of note, given that renal excretion is the main route of linezolid clearance (5), 6 of the 12 patients receiving hemodialysis developed thrombocytopenia versus 7/32 nonhemodialysis patients (P ϭ 0.07, chi-square test) (Table 2), suggesting that drug or metabolite accumulation may play a role in this AR, despite the fact that linezolid is known to be removed by conventional intermittent hemodialysis (6). Unfortunately, no serum drug or metabolite levels were collected from our patients to assess this issue more closely, but it is the subject of currently ongoing research by our group.…”
mentioning
confidence: 99%
“…Moreover, in intensive care units (ICUs), extended dialysis (ED), a hybrid of continuous and intermittent renal replacement therapy (RRT), is increasingly used throughout the world (4-7). ED removes various antibiotics more efficiently compared with standard intermittent hemodialysis (IHD) three times a week or continuous RRT (8)(9)(10)(11)(12)(13), as very recently reviewed by Bogard et al (14). A single report from a patient with AKI suggests that higher doses of ampicillin/ sulbactam might also be necessary for critically ill patients treated with ED compared with intermittent hemodialysis (IHD) in the outpatient setting (15).…”
Section: Introductionmentioning
confidence: 97%